Analisis Kebutuhan Asesmen Working Memory dalam Pembelajaran Fisika di Sekolah Inklusif: Kajian Literatur - Sari, Lasmita; Novia, Hera; Fatimatuzzahra, Ana; Arifiyanti, Fitria (Pendidikan Fisika Universitas Nurul Huda, 2025)
Working memory (WM) assessment plays a vital role in supporting physics learning within inclusive classrooms that serve students with diverse learning needs. This study examines the necessity of WM assessment through a systematic literature review. WM is responsible for temporarily storing and manipulating information, which is crucial for understanding complex physics concepts. Students with limited WM capacity often struggle to follow instructions and complete problem-solving tasks. Inclusive classrooms face challenges due to varied learning needs and the lack of valid and reliable assessment tools. Instruments such as the Wechsler Memory Scale and the Automated Working memory Assessment (AWMA) are recommended for accurately measuring WM capacity. Teaching strategies that incorporate visual supports and reduce cognitive load have proven effective in accommodating WM limitations. While computer-based WM training shows promise, direct classroom interventions are considered more effective in the long term. This study recommends ongoing WM assessment, tailored instructional strategies, supportive learning materials, and collaboration between teachers and professionals to create a more adaptive and inclusive physics learning environment